2013
DOI: 10.1182/blood-2012-08-447136
|View full text |Cite
|
Sign up to set email alerts
|

Naturally secreted immunoglobulins limit B1 and MZ B-cell numbers through a microbiota-independent mechanism

Abstract: Key Points• The study of AID 2/2 mS 2/2 mice reveals a microbiotaindependent negative feedback control of MZ and B1 cell numbers by naturally secreted Ig. CD1382 plasmablast-like cells; and 4) overexpression of IgM in several cell subsets.Complementation experiments based on either mixed bone marrow reconstitution of chimeras or Ig infusion, and analysis of mice raised in germ-free conditions reveal a negative feedback mechanism in which MZ and B1 cell numbers are under the control of naturally secreted Igs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
4
14
0
1
Order By: Relevance
“…Fig. 1B), as expected for this treatment regimen (5961). Thus, while PD-L2 −/− and WT weanling mice (4 weeks of age) begin with equivalent PC-specific Ab levels in the serum, altered host microbiota is unlikely to explain the appearance or maintenance of enhanced PC-specific Ab levels in PD-L2 −/− mice.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Fig. 1B), as expected for this treatment regimen (5961). Thus, while PD-L2 −/− and WT weanling mice (4 weeks of age) begin with equivalent PC-specific Ab levels in the serum, altered host microbiota is unlikely to explain the appearance or maintenance of enhanced PC-specific Ab levels in PD-L2 −/− mice.…”
Section: Resultssupporting
confidence: 85%
“…Whereas B-2 cells rely heavily on cognate MHC Class II:TCR interactions (among others), B-1 cells secrete Abs in the absence of MHC-dependent signals. Natural Ab production is thought to be driven by endogenous Ags and regulated via anti-idiotype Abs (2, 14, 61, 75, 112115) and specific cytokines like IL-5 (30, 81, 116). Progenitor population and anatomical location play an important role in B-1 cell development, and the existence of other mechanisms of control include microenvironment, surface molecules, and intracellular signal transducers (23, 89, 117124).…”
Section: Discussionmentioning
confidence: 99%
“…Various earlier studies reported increases in CD5+ B-1a cell subsets in the peritoneal cavity of μs−/− mice. 43,83,84 While our studies confirmed increased frequencies and numbers of CD5+ B cells in spleen and peritoneal cavity, the CD5+ cells were CD43 neg CD45R hi and CD19 int , thus distinct in phenotype from that of B-1a cells. In addition, these CD5+ B cells were short-lived and unresponsive to BCR-mediated stimulation, suggesting that they are anergic B cells that escape central tolerance induction in the bone marrow.…”
Section: Natural Igm Controls B-cell Development and Selectionsupporting
confidence: 60%
“…Indeed, mice genetically engineered to lack secreted, but not membrane-bound IgM (sIgM), were originally reported to harbor increased frequencies of peritoneal cavity B-1a cells (67, 68), suggesting that the presence of secreted IgM might control B-1 cell development. Similarly, a recent study suggested that natural antibody production regulates the size of the B-1 cell compartment (69). However, with regards to the former study, multiple lines of evidence demonstrated that the accumulating CD5+ B cells in the body cavities of sIgM−/− mice, previously identified as B-1a, were not B-1 cells, but anergic B cells: Phenotypic analysis showed that they lacked surface expression of CD43, a hallmark of many albeit not all B-1 cells (70), that they did not express high levels of CD19, characteristic of B-1a cells, and they nearly completely lacked cells binding to liposomes containing phosphatidylcholine (PtC), a predominant B-1a cell specificity encoded by VH11 or VH12, genes that were not expressed by peritoneal cavity B cells in sIgM−/− mice (71).…”
Section: B-1 Cell Repertoire Selection and Maintenancementioning
confidence: 93%